Colquhounia Root Tablet Protects Rat Pulmonary Microvascular Endothelial Cells against TNF-α-Induced Injury by Upregulating the Expression of Tight Junction Proteins Claudin-5 and ZO-1. (18th November 2018) - Zhou, Wenjie; Shi, Guocui; Bai, Jijia; Ma, Shenmao; Liu, Qinfu; Ma, Xigang
Abstract : Background. There are currently limited effective pharmacotherapy agents for acute lung injury (ALI). Inflammatory response in the lungs is the main pathophysiological process of ALI. Our preliminary data have shown that colquhounia root tablet (CRT), a natural herbal medicine, alleviates the pulmonary inflammatory responses and edema in a rat model with oleic acid-induced ALI. However, the potential molecular action mechanisms underlining its protective effects against ALI are poorly understood. This study aimed to investigate the effects and mechanism of CRT in rat pulmonary microvascular endothelial cells (PMEC) with TNF- α -induced injury. Methods. PMECs were divided into 6 groups: normal control, TNF- α (10 ng/mL TNF- α ), Dex (1×10 - 6 M Dex + 10 ng/mL TNF- α ), CRT high (1000 ng/mL CRT + 10 ng/mL TNF- α ), CRT medium (500 ng/mL CRT + 10 ng/mL TNF- α ), and CRT low group (250 ng/mL CRT + 10 ng/mL TNF- α ). Cell proliferation and apoptosis were detected by MTT assay and flow cytometry. Cell micromorphology was observed under transmission electron microscope. The localization and expression of tight junction proteins Claudin-5 and ZO-1 were analyzed by immunofluorescence staining and Western blot, respectively. Results. TNF-a had successfully induced an acute endothelial cell injury model. Dex and CRT treatments had significantly stimulated the growth and reduced the apoptosis of PMECs (all p < 0.05 or 0.01) and alleviated the TNF- α -induced cell injury. The expression of Claudin-5 and ZO-1 in Dex and all 3 CRT groups was markedly increased compared with TNF-a group (all p < 0.05 or 0.01). Conclusion. CRT effectively protects PMECs from TNF- α -induced injury, which might be mediated via stabilizing the structure of tight junction. CRT might be a promising, effective, and safe therapeutic agent for the treatment of ALI.